Trace determination of cobalt in biological fluids based on preconcentration with a new competitive ligand using dispersive liquid-liquid microextraction combined with slotted quartz tube-flame atomic absorption spectrophotometry - Er, Elif Orturk; Bakirdere, Emine Gulhan; Unutkan, Tugce; Bakirdere, Sezgin (ELSEVIER GMBH, URBAN & FISCHER VERLAG, 2018)
A new competitive ligand has been synthesized for the preconcentration to obtain lower detection limits by using dispersive liquid-liquid microextraction combined with slotted quartz tube-flame atomic absorption spectrophotometry (DLLME-SQT-FAAS). The proposed method is simple, eco-friendly and has high sensitivity. The preconcentration procedure was optimized on the basis of various parameters affecting the complex formation and extraction efficiency such as pH and volume of buffer solution, volume of ligand solution, mixing period, volume and type of extraction solvent, volume and type of dispersive solvent, and salt effect. Instrumental parameters were also optimized to get higher sensitivity. Under the optimum conditions, the calibration graph was linear in the range of 10-250 ng mL(-1) land the resulted limits of detection and quantification (LOD and LOQ) for combined method were 4.7 and 15.7 ng(-1) mL(-1), respectively. The detection power was improved 48-fold using DLLME-SQT-FAAS method compared to conventional FAAS. The precision of the method was found to be high with a relative standard deviation of 2.5%. The accuracy of method was evaluated by recovery experiments using matrix matching study on spiked urine and blood samples. The recoveries for urine and blood samples ranged from 99.8 to 108.9% and 102.5 to 110.0%, respectively.
Keywords: Cobalt; Dispersive liquid-liquid microextraction; Slotted quartz tube; Atomic absorption spectrometry; Blood; Urine; SOLID-PHASE EXTRACTION; CLOUD POINT EXTRACTION; WATER SAMPLES; SPECTROMETRIC DETERMINATION; ICP-MS; NICKEL; COPPER; ZINC; LEAD; FOOD; Biochemistry & Molecular Biology; Endocrinology & Metabolism